Johann Stamitz und die europäische Musikermigration im 18. Jahrhundert - Fabian, Sarah-Denise; Leopold, Silke; Mücke, Panja; Thomsen-Fürst, Rüdiger (Schriften zur Südwestdeutschen Hofmusik, 2021)
This publication documents the papers presented at the symposium "The Stamitz family and European musician migration in the 18th century", which took place in Schwetzingen on 17 and 18 June 2017 on the occasion of the 300th birthday of Johann Stamitz. The conference was organised by the Research Centre for the History of Southwest German Court Music of the Heidelberg Academy of Sciences and the Mannheim State University of Music and Performing Arts. Johann Stamitz, a figurehead of Mannheim's court music, and his family are exemplary for the musician migration of the eighteenth century in Central Europe. Based on this, the papers will examine various aspects of the topic. It was part of the conference's concept to offer not only experienced experts in this field but also young scholars a platform for their own research and for the presentation of the results.